Morus alba and Morus rubra alleviate hepatic disorder, oxidative DNA damage and gene expression profile change in obese rats - Howaida Ibrahim Abd-Alla (Journal of Global Pharma Technology, 2019)
Objective: To examine the impact of Morus rubra and Morus alba extracts on physiological and metabolic functions of obese male rats induced by high fat diet. Methods: Orlistat was used as standard drug. Seventy Wistar male rats (weighing 150-160 g) were fed for 12 weeks with high fat diet to induce obesity. The obese rats were randomly assigned to three groups (10 rats each) and treated with Morus rubra and Morus alba extracts or orlistat for 6 consecutive weeks. The level of visfatin was measured by enzyme-linked-immunosorbent. The suppression impact of extracts against DNA adducts 8-hydroxy-2′-deoxyguanosine (8-OHdG) and 2-deoxyguanosine (2-dG) generation was measured by high-performance liquid chromatography. Expression of genes including ATP- citrate-lyase, peroxisome-proliferator-activated receptor-γ and HMG CoA reductase in liver tissues were also measured by quantitative real time-polymerase chain reaction. Results: Treatment with the Morus rubra and Morus alba extracts and orlistat significantly decreased visfatin level. Morus rubra and Morus alba extracts significantly decreased the levels of mRNA expression of ATP-citrate-lyase, HMG CoA reductase genes, and peroxisome-proliferator-activated receptor-γ compared with high fat diet rats. In addition, Morus rubra and Morus alba extracts decreased the level of 8-OHdG/2-dG ratio. Conclusions: The ameliorating effect of Morus rubra and Morus alba extracts on visfatin levels reducing fat may be attributed to the rich content of polyphenolic which suppresses lipid synthesis in liver tissues. Moreover, anti-DNA damage effect of Morus rubra and Morus alba extracts suggests their role as natural antioxidants against diseases such as obesity associated with genetic damage.